Development of problem based learning training module in nursing education - P., Sathya; Reddemma, K. (International Journal of Research in Medical Sciences, 2017)
Background: Problem based learning (PBL) is an innovative way of delivering instruction in which problems are used as the basis of learning. PBL method of teaching enhances the skill of Nursing students and there by improves delivery of patient care. It is a responsibility of Nurse Educators to prepare the Nursing students to face the world of reality. The study, aimed to develop and train the post graduate Nursing faculty on PBL method of teaching. Methods: In Phase I Training module in Problem Based Learning was developed through extensive review of literature, experts’ guidance and from the clinical records. In Phase II using pre-experimental one group pretest posttest design two days training on PBL was implemented. Results: PBL training module was developed and validated in the phase I of the study. Content validity index (CVI) was found to be above 0.88 in all the aspects of the module. PBL workshop conducted was found to be effective in terms of improvement in the mean post-test knowledge score (13.33±1.69) compared to the mean pre-test knowledge score (9.33±4.10) though it was not statistically significant. All three-faculty had satisfactory mean score of above 3 in all the areas. Conclusions: Faculty expressed their satisfaction and gave positive feedback on the effectiveness of PBL module in terms of its content, course delivery and the practical session.